Rendimiento de híbridos comerciales de maíz amarillo duro (zea mays l.) bajo riego en el distrito de Buenos Aires – provincia de Picota - región San Martín - Escudero Tanchiva, Rocio (2009)
Present labor is I realized between October of 1999 until February of the 2000, in the district of Buenos Aires, Province of Picota - Region San Martín, placed to OS° 48' 15" south latitude, 76°06'S8" west length and to an altitude of 223 meters on level of the sea. It is labor with 8 hybrid that they are: NK-STAR, C-606, C-425, DK-821, AG-612, AG5572, G-5423 and PIMTE-INIA (witness). It is appraisement the efficiency and other complementary vegetative characteristics, employing the statistic design of full block at random with 8 treatrnents and 4 repetitions, whose results were analyzed through the variance analysis, the proof of Duncan and the linear regression analysis to the 1 and 5% of probability. Experimental soil was clayey franc texture, of slightly alkaline reaction (potential Hydrogen : 7,79), with organizational matter content, middle, ( 2,75 ), middle phosphorus content (13 ppm) and under potassium content (0,28meq). The sowing is I realized in wet land, being employed a distancing of 0,85 m between ruts by 0,50 m between plants, letting two plants by blow, making a density by hectare of 47 058 plants. The cultivation received 4 irrigation's under the system by aspersion and the guaranty was made employing 250 sulfate Kilograms of amónico, 100 Kg of phosphate di- amónico, 100 Kg. of potassium sulfate, to the moment of the emergency of the plants and 150 Kg of úrea to 30 days after. According to the results of the statistic analysis was found differences highly meaningful for the treatments of grain efficiency 14% of dampness, due to the genetic differences of the genotypes experimental whose efficiencies fluctuated between 6,8483 TM/hectare. to 4,6771 TM/there has that corresponded to the hybrid AG-612 and PIMTE-INIA respectively. 3ointly with the hybrid AG-612 emphasized by its greater efficiency the following hybrid: C-425, G - 5423 and NK-STAR, between those which did not exist meaningful differences, surpassing to the variety PIMTE, that I reach an efficiency of 4,6771 TM/hectare has., being located in the I murder post in the merit order. The better hybrid four in grain efficiency is recommended to sow in the zone and other localities with characteristic of soil and climate, similar to the experimental site.